Pharmacodynamic evaluation of intermittent versus extended and continuous infusions of piperacillin/tazobactam in a hollow-fibre infection model against Klebsiella pneumoniae. (25th June 2020) - Sumi, Chandra Datta; Heffernan, Aaron J; Naicker, Saiyuri; Islam, Kamrul; Cottrell, Kyra; Wallis, Steven C; Lipman, Jeffrey; Harris, Patrick N A; Sime, Fekade B; Roberts, Jason A
Abstract: Objectives: To compare bacterial killing and the emergence of resistance to piperacillin/tazobactam, administered by intermittent versus prolonged infusion (i.e. extended or continuous), for ceftriaxone-resistant Klebsiella pneumoniae clinical isolates in an in vitro dynamic hollow-fibre infection model (HFIM). Methods: K. pneumoniae 68 (Kp68; MIC = 8 mg/L, producing SHV-106 and DHA-1) and K. pneumoniae 69 (Kp69; MIC = 1 mg/L, producing CTX-M-14) were studied in the HFIM over 7 days (initial inoculum ~10 7  cfu/mL). Six piperacillin/tazobactam dosing regimens for Kp68 (4/0.5 g 8 hourly as 0.5 and 4 h infusions, 12/1.5 g/24 h continuous infusion, 4/0.5 g 6 hourly as 0.5 and 3 h infusions and 16/2 g/24 h continuous infusion) and three piperacillin/tazobactam dosing regimens for Kp69 (4/0.5 g 8 hourly as 0.5 and 4 h infusions and 12/1.5 g/24 h continuous infusion) were simulated (piperacillin clearance = 14 L/h, creatinine clearance = 100 mL/min). Total and resistant populations and MICs were quantified/determined. Results: For Kp68, all simulated dosing regimens exhibited approximately 4 log10 of bacterial killing at 8 h followed by regrowth to approximately 10 11  cfu/mL within 24 h. The MICs for resistant subpopulations exceeded 256 mg/L at 72 h. Similarly, for Kp69, all simulated dosing regimens exhibited approximately 4 log10 of bacterial killing over 8 h; however, only the continuous infusion prevented bacterial regrowth. Conclusions: Compared with intermittent infusion, prolonged infusion did not increase initial bacterial killing and suppression of regrowth of plasmid-mediated AmpC- and ESBL-producing K. pneumoniae . However, continuous infusion may suppress regrowth of some ESBL-producing susceptible K. pneumoniae, although more data are warranted to confirm this observation.